Assessing Competitive Strategies in UK Manufacturing SMEs - Michail, Antonios (Business Management and Strategy, 2024)
In this comprehensive study, we delve into an exhaustive examination of effective competitive strategies tailored for small to medium-sized enterprises (SMEs). The principal objective of this research centers on scrutinizing the strategic orientation of UK Manufacturing SMEs. Conducting an extensive literature review, we critically evaluated Porter’s framework and identified several gaps in its applicability. Notably, critiques assert that the model inadequately captures the intricate nature of strategic behavior within real organizations and fails to provide a fully accurate representation of strategy-performance relationships. Empirical research further highlights the model’s limitations, indicating its inability to facilitate the desirable combination of competitive strategies by firms. To address the outlined objectives, we employed a semi-structured questionnaire in our investigation. The ensuing analysis involved the application of factor and cluster analysis to identify strategic variables currently employed by SMEs in the manufacturing domain. Our data analysis revealed a divergence from the adoption of Porter’s single generic strategies. Instead, the findings supported the utilization of mixed strategies that integrate elements from both differentiation and low-cost strategies. Significantly, these hybrid approaches were found to be associated with enhanced firm performance. This study contributes valuable insights into the nuanced landscape of competitive strategies within the UK SMEs, shedding light on the dynamic interplay between strategic choices and firm performance.